Local scour due to submerged horizontal jet / Salim Keteron - Keteron, Salim (1996)
This study is concerned with an experimental investigation of the scour phenomena and sediment transport due to a two-dimensional submerged horizontal jet of water issuing from a sluice gate and flowing over a rigid apron to an erodible bed. This study was carried out in the wave flume in the Hydraulic Laboratory of The School of Civil Engineering, MARA Institute of Technology, Shah Alam . Based on experimental data the scour characteristics have been tested using the formula developed by Chatterjee and Ghosh (1994) and then the comparison between the experimental result and the theory has been made based on Chatterjee and Ghosh (1994) equation as used in the time to reach equilibrium stage, the volume of scour at any time, the locations of maximum scour depth and peak of dune, and the variation of maximum scour depth with time.